AI-based Neural Networks for Gas-Sensor Sensitivity and Response-Time Prediction - Maznouk, Noura (Journal of Pure & Applied Sciences, 2025)
In this study, three types of gas sensors were fabricated using thin-film technology: tin oxide doped with tungsten (SnO₂+WO₃), tin oxide doped with zinc oxide (SnO₂+ZnO), and tungsten oxide doped with zinc oxide (WO₃+ZnO). These sensors were synthesised with multiple doping ratios and operated at two temperatures (250 °C and 350 °C). They were exposed to acetone and ethanol vapours at a concentration of 500 ppm, and measurements were recorded for sensitivity response (S) and response time (t). Three neural network models were developed using artificial intelligence to predict sensitivity and response time: individual neural models for each sensor; an early fusion model that combines inputs and outputs into a unified network; and a late fusion model that separates each task into an independent subnetwork. The models were trained using MATLAB’s nntraintool and evaluated using quantitative metrics (MAE, RMSE, R², MAPE) and training/visual indicators such as performance curves, gradient, mu, error histogram, and regression plots. Randomisation was fixed to ensure consistent data distribution across training, validation, and testing sets, enabling fair comparisons between the models under equal experimental conditions. The results showed that the individual model for the SnO₂+WO₃ sensor achieved the highest accuracy in sensitivity prediction, while the WO₃+ZnO model excelled in response time estimation. The late fusion model demonstrated the most balanced and reliable performance, with the lowest error rates and highest correlation coefficients, confirming its strong generalisation capability. In contrast, the early fusion model showed good training performance but limited generalisation, particularly in predicting response time. This study presents a novel framework for intelligent prediction of gas sensor behaviour, combining experimental validation with neural modelling. It offers a valuable contribution to the development of accurate and generalisable sensing systems for industrial and smart environments.